Treatment of Tobacco Use Disorders in Smokers with Serious Mental Illness: Toward Clinical Best Practices. Issue 2 (March 2015) - Evins, A. Eden; Cather, Corinne; Laffer, Alexandra
Abstract : Abstract: Addiction to tobacco-derived nicotine remains highly prevalent in the United States, with 18% using daily, and 53% of those with serious mental illness using daily. While smokers with serious mental illness have been excluded from most large nicotine-dependence treatment studies, a growing evidence base is available to guide clinicians in assisting their patients with psychiatric illness to quit smoking. The aim of this review is to present the evidence on safety and efficacy of smoking cessation interventions for those with serious mental illness. Smokers with schizophrenia spectrum disorders should receive varenicline or bupropion with or without nicotine replacement therapy in combination with behavioral treatment. Although more research is needed, preliminary evidence suggests that varenicline in combination with behavioral support is efficacious and well tolerated for smoking cessation for those with bipolar disorder and major depressive disorder. Controlled trials have found no evidence that in patients with serious mental illness, the use of pharmacotherapeutic cessation aids worsens psychiatric symptoms or increases the rate of psychiatric adverse events. Converging evidence indicates that a majority of smokers with serious mental illness want to quit smoking and that available pharmacotherapeutic cessation aids combined with behavioral support are both effective for, and well tolerated by, these smokers.